SYNERGISTIC INTERACTION OF EPINEPHRINE AND CALCIUM IONOPHORE IN PLATELET AGGREGATION - Butt, Idrees Farooq; Saeed, Sheikh Arshad; Waqar, Saima N; Aslam, Muhammad (Journal of Ayub Medical College Abbottabad, 2005)
Background: Platelets play a key role in haemostasis. Human Platelets contain a2 adrenergic receptors, which are coupled with guanine nucleotide proteins (G proteins). The platelet activation involves a number of receptors for agonists. It has also been shown that most of the agonists act in synergy and potentiate the effects of each other. The present experimental study was designed to study the potentiation of epinephrine on human platelets by calcium ionophore A23187 and the possible role of calcium in platelet aggregation as a second messenger. Methods: Study was carried out at Department of Biological Sciences Aga Khan University, Karachi. Blood samples from healthy volunteers were collected; Platelet aggregation was measured using Dual channel Lumi Aggregometer. The chemicals used include epinephrine, calcium ionophore A23187, yohimbine, diltiazem, verapamil and S Nitrosoacetylpenicillamin (SNAP).Results: Epinephrine at low concentrations (0.01 - 0.2 mM) and/or A23187 (0.1-0.5 mM) itself did not produce platelet aggregation. However, when added together, a marked potentiation of platelet aggregation was observed. This synergistic effect was inhibited by a2-receptor blocker yohimbine; (IC50 = 0.05 mM) showing that the response is receptor mediated. To find out the molecular basis of this potentiation, we used SNAP, a nitric oxide donor and Ca++ channel blockers,i.e. diltiazem and verapamil. The SNAP, diltiazem and verapamil inhibited the platelet aggregation induced by A23187 and epinephrine with IC50 value of 0.5 mM, 50mM and 22mM respectively. Conclusion: The results of the study suggest that epinephrine and calcium ionophore act synergistically and Ca++ plays an important role in this synergistic interaction. While calcium channels blocking drugs diltiazem and verapamil inhibit this synergism. Key Words: Platelet aggregation, Epinephrine, calcium ionophore A23187, yohimbine, diltiazem, verapamil and SNAP.